Crack Damage in Polymers and Composites: A Review. (2nd January 2016) - Naebe, Minoo; Abolhasani, Mohammad Mahdi; Khayyam, Hamid; Amini, Abbas; Fox, Bronwyn
Abstract : Polymer-based materials are extensively used in various applications such as aircrafts, civilian structures, oil and gas platforms and electronics. They are, however, inherently damage prone and over time, the formation of cracks and microscopic damages influences the thermo-mechanical and electrical properties, which eventually results in the total failure of the materials. This paper provides an overview of the principal causes of cracking in polymer and composites and summarizes the recent progress in the development of non-destructive techniques in crack detection. Furthermore, recent progress in the development of bio-inspired self-healing methods in autonomic repair is discussed.